Spectrophotometric Determination of Metoclopramide Hydrochloride in Pharmaceutical Formulations Using Diazotization Coupling Reaction - Yassin, Rabee Mohammed Ali; Othman, Nabeel Sabeh (Iraqi Journal of Science, 2023)
For the determination of metoclopramide hydrochloride (MCPD) in pharmaceutical formulations, a rapid and straightforward spectrophotometric method has been proposed. The method involves diazotizing the main amino group of MCPD with sodium nitrite followed by coupling reaction with reagent 1,7-Dihydroxynaphthalene (1,7-DHN) to form a stable and colored compound in alkaline medium of sodium hydroxide which showed a maximum absorbance‎ intensity at the wavelength 578 nm. The linearity of developed method has ranged from 1.0 - 15 ‎ µg.ml-1‎‎ while the molar absorptivity 2.9867x104 l.mol-1.cm-1, RSD% was less than 1.11%. While the LOD and LOQ were 0.059 ‎µg.ml-1‎‎ and 0.198 ‎ µg.ml-1‎‎ respectively. The method is appropriate for the determination of MCPD in the presence of other substances that are typically included in dosage forms.